PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MEDIA FILM KRITIK SOSIAL - Purwaningsih, Uni (Metafora: Education, Social Sciences and Humanities Journal, 2016)
Writing poetry is one of the subjects of Literature appears logical competencies that must be accomplished high school students. But in fact learning to write poetry is still considered low, especially among students of class XI SMA NI Paciran language. The problem in this research are (1) how the implementation of the learning process is by using the medium of film of social criticism (2) how to increase writing skills to use traditional media poetry films of social criticism among students of class XI SMA Negeri I Paciran language. This research is a class act who performed two cycles. Subjects were students of class XI SMA Language Paciran 2014-2015 school year. Number of students 19 children, with details of 2 men and 17 women. Data obtained through observation, Interview, questionnaire, and test. Based on the results of this study concluded that the use of social media movie critics can improve the skills of teachers in learning to write poetry, the activities of learners and improve the skills of learners writing poetry.Â